2017
DOI: 10.1159/000486777
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Nomenclature and Cytological Characterization of Sacred Lotus

Abstract: Sacred lotus is a basal eudicot plant that has been cultivated in Asia for over 7,000 years for its agricultural, ornamental, religious, and medicinal importance. A notable characteristic of lotus is the seed longevity. Extensive endeavors have been devoted to dissect its genome assembly, including the variety China Antique, which germinated from a 1,300-year-old seed. Here, cytogenetic markers representing the 10 largest megascaffolds, which constitute approximately 70% of the lotus genome assembly, were deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
(51 reference statements)
1
6
0
Order By: Relevance
“…For megascaffolds 6, blocks 10A, 10C and 2E were reassembled as a new megascaffold (Figure S1). Similar results were also observed by uorescence in situ hybridization (FISH) analysis in lotus (Meng et al 2017). The FISH assay also revealed that megascaffolds 1-10 were assigned to eight chromosomes.…”
Section: Discussionsupporting
confidence: 82%
“…For megascaffolds 6, blocks 10A, 10C and 2E were reassembled as a new megascaffold (Figure S1). Similar results were also observed by uorescence in situ hybridization (FISH) analysis in lotus (Meng et al 2017). The FISH assay also revealed that megascaffolds 1-10 were assigned to eight chromosomes.…”
Section: Discussionsupporting
confidence: 82%
“…Analysis of the Nelumbo nucifera genome sequence suggest that, after the lineage-specific whole-genome duplication event (approximately 18 to 76 million years ago), several rearrangements (i.e., ancestral chromosome fissions, fusions, and a single inversion) were responsible for the modern diploid karyotype (16 chromosomes) [ 67 , 68 ]. The sacred lotus genome is ~1 Gb in size and encodes approximately 27,000 genes [ 1 , 2 ].…”
Section: Bia Biosynthetic Genes and Enzymes In The Sacred Lotusmentioning
confidence: 99%
“…Many researchers suggest that N. komarovii is a Far Eastern race of N. nucifera Gaertn., widely used in medicine, and as a delicacy in Chinese and Japanese cuisine. Karyotype study revealed the same chromosome number (2n = 16) in N. nucifera (Diao et al 2005, 2006, 2011, Meng et al 2017, Ming et al 2013, Yang et al 1998. Our data on the morphology of N. komarovii chromosomes are confirmed by studies of Chinese scientists (Meng et al 2017).…”
Section: Resultsmentioning
confidence: 96%